Complex medical conditions and health risk behaviors among homeless males with schizophrenia - Rojanaworarit, Chanapong; Songsiripradubboon, Siriporn; Worahan, Viparut; Kerdpon, Piyarat; Photisan, Nuttawoot (Narra J, 2025)
A comprehensive assessment of complex medical conditions and health risk behaviors among homeless individuals with schizophrenia facilitates the identification of health needs and areas for improvement in health services, thereby promoting more holistic care for this highly vulnerable population. The aim of this study was to assess complex medical conditions and health risk behaviors among Thai homeless males with schizophrenia. Additionally, factors related to the presence of multimorbidity in these vulnerable individuals were explored. Using a cross-sectional design, the study identified the prevalence of systemic diseases, physical disabilities, co-occurring mental disorders, and health risk behaviors among Thai homeless males with schizophrenia at the largest public homeless shelter in Pathum Thani, Thailand. Factors related to the presence of multimorbidity among these individuals were analyzed using univariable and multivariable generalized linear models for binomial response data with an identity link function to estimate prevalence difference (PD). Among 231 homeless males with schizophrenia, the prevalence of multimorbidity was 35.9%. Disease-specific prevalence was dominated by epilepsy (21.6%) and anemia (10.8%). About 38.4% of participants were underweight. The most common health risk behaviors included smoking (71.5%) and alcohol consumption (23.7%). Physical disabilities and co-occurring mental disorders were identified in 11.7% of participants, while 5.7% reported a history of suicide attempts. Underweight individuals had a significantly higher prevalence of multimorbidity compared to those with normal weight (adjusted PD (95%CI): 0.150 (0.017–0.823)). The study highlights that the substantial burden of complex medical conditions and health risk behaviors in this population underscores the need for a healthcare system that is not only reactive but also proactive. Such a system should prioritize health promotion and disease prevention to effectively safeguard the well-being of these vulnerable individuals.